Conceptual framework factors affecting construction labour productivity - Nurhendi, Revianty Nurmeyliandari; Muhamad Azry Khoiry,; Noraini Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Productivity is one means to measure the efficiency of a construction project. Most of the problems that are always encountered in construction projects are problems related to labour productivity. Labour productivity has become part of the issues that significantly affect the construction project (CP) performance (cost, quality, and time). Labour turn into the most significant productive resource in achieving profitability and successful project. Based on previous investigations, the amount of costs spent on workers is above 30 % of the total cost of the overall project. So it is essential to pay attention to the increase in productivity of construction labour. Labour performance in the construction business remains an indicator of competitiveness and achievement in the construction company. Therefore, by focusing on the productivity of the construction labour, it is very likely that a construction company can achieve a higher level of project completion, more economical construction costs, and control the performance of the ongoing project. One way to increase the productivity of construction labour then requires an understanding of the factors that influence labour productivity. To achieve the increasing construction labour productivity (CLP), it needs a conceptual framework of variables in the form of affecting factors in the CLP. The conceptual framework is obtained by conducting a literature review of related articles from indexed journals and contributions from construction management practitioners in Indonesia. The concept of this framework was built for future research by making a model of CLP.